The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1523/jneurosci.2680-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Uncharacteristic Task-Evoked Pupillary Responses Implicate Atypical Locus Ceruleus Activity in Autism

Abstract: Autism spectrum disorder (ASD) is characterized partly by atypical attentional engagement, reflected in exaggerated and variable responses to sensory stimuli. Attentional engagement is known to be regulated by the locus ceruleus (LC). Moderate baseline LC activity globally dampens neural responsivity and is associated with adaptive deployment and narrowing of attention to task-relevant stimuli. In contrast, increased baseline LC activity enhances neural responsivity across cortex and widening of attention to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
1
26
1
Order By: Relevance
“…Cortical gain increases behavioural flexibility, exploration of the task environment and as such to relevant and irrelevant stimuli. When phasic responses decrease, the focus shifts only to task-relevant stimuli, according to Granovetter et al (Granovetter et al, 2020). In their study, the ASD group showed inflexibility of regulation of the LC activity, they conclude based on a lower pupil reactivity in the presence of distractions, which is not expected when the LC would be regulated correctly.…”
Section: Ansmentioning
confidence: 84%
See 2 more Smart Citations
“…Cortical gain increases behavioural flexibility, exploration of the task environment and as such to relevant and irrelevant stimuli. When phasic responses decrease, the focus shifts only to task-relevant stimuli, according to Granovetter et al (Granovetter et al, 2020). In their study, the ASD group showed inflexibility of regulation of the LC activity, they conclude based on a lower pupil reactivity in the presence of distractions, which is not expected when the LC would be regulated correctly.…”
Section: Ansmentioning
confidence: 84%
“…Laeng et al (2018) hypothesized this constriction would be reduced or absent in the ASD group, but found no differences between the ASD and the TD group. The inability to distinguish relevant from irrelevant stimuli as found by Granovetter et al (2020) impedes the creation of priors and expectations and the ability to learn from novel environmental input and consequently could cause increased attention to particular environmental stimuli that other don't consider relevant and this explain the fixated interests in ASD, as well as increased sensitivity to sensory stimuli. They confirmed this in their results, as a smaller pupil response amplitude, which shows low phasic LC activity and increased cortical gain, was associated higher ADOS-RRB scores (Granovetter et al, 2020).…”
Section: Processing Of Emotional Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, elevation in tonic pupil size has also been found in children with ASD [36,37] (but see [38]). On the other hand, findings on phasic pupil response in individuals with ASD are inconclusive [37][38][39]. As ADHD is the most common comorbidity in children with ASD [40,41], it is possible that ADHD traits might play an important role in atypical pupillary responses in ASD.…”
Section: Plos Onementioning
confidence: 99%
“…A recent review suggests that atypical pupillary responses in autism spectrum disorder (ASD) might be associated with atypical attentional functions [35]. For example, elevation in tonic pupil size has also been found in children with ASD [36,37] (but see [38]). On the other hand, findings on phasic pupil response in individuals with ASD are inconclusive [37][38][39].…”
Section: Plos Onementioning
confidence: 99%